2012
DOI: 10.1097/nna.0b013e31824ccd7b
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership Practices of Chief Nursing Officers in Magnet® Organizations

Abstract: As CNOs gain experience and education, they exhibit more transformational leadership characteristics. Magnet organizations should take steps to retain CNOs and support their development and advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 19 publications
4
26
1
2
Order By: Relevance
“…Surprisingly, the clinical ladder nurses with more years of RN experience reported fewer leadership behaviors. This is in direct contrast to the findings of Clavelle et al (2012). There is a need to address the educational gap of leadership training and to evaluate the obstacles that may be preventing frontline staff nurses from leading their patients to better health care outcomes.…”
Section: 79contrasting
confidence: 47%
See 2 more Smart Citations
“…Surprisingly, the clinical ladder nurses with more years of RN experience reported fewer leadership behaviors. This is in direct contrast to the findings of Clavelle et al (2012). There is a need to address the educational gap of leadership training and to evaluate the obstacles that may be preventing frontline staff nurses from leading their patients to better health care outcomes.…”
Section: 79contrasting
confidence: 47%
“…Study results noted greater transformational leadership behaviors with years of nursing leadership experience and advanced education, but the opposite was found in the current study relative to clinical ladder nurses. "Enabling others to act" and "modeling the way" were the top two practices of the chief nursing officers (Clavelle, Drenkard, Tullai-McGuinness, & Fitzpatrick, 2012).…”
Section: 79mentioning
confidence: 99%
See 1 more Smart Citation
“…A model of five practices for exemplary leadership under the influence of transformational leadership (6) was proposed to corroborate these steps: model the way; inspire a shared vision; challenge the process; enable others to act; and encourage the heart. The theoretical model of these practices is internationally recognized for leadership development in different productive segments, and more recently several studies have pointed out its potential for nursing leadership-that is, to assess behaviors associated with the leadership of nurses (7)(8)(9) . It is important to point out that this study found that although the leadership practices have a common basis for managers, there is a need for an approach contextualized to the specificity of the health productive and managerial process, particularly in nursing, as it differs from other segments.…”
Section: Introductionmentioning
confidence: 99%
“…A liderança transformacional é constantemente desafiada a promover uma gestão adequada, considerando a implementação da tecnologia da informação e a concepção de novos modelos de cuidado advindos da modernidade. Para tanto, torna-se fundamental que desenvolva uma forte visão e filosofia organizacional, de maneira a atender (43) .…”
Section: Quadro 1)unclassified